OFFSET
0,3
COMMENTS
Let H(x) equal the i-th iteration of (x + x^2), then
. the inverse of H(x) equals the conjugate of H(x);
. H(x+x^2) = H(x) + H(x)^2;
. H(x) = F(x) + i*G(x) where F(x) = e.g.f. of A179200 and G(x) = e.g.f. of this sequence, where H(F(x) - i*G(x)) = x;
FORMULA
E.g.f.: G(x) satisfies:
. G(x) = sqrt( F(x) + F(x)^2 - F(x+x^2) )
. F(x) = (G(x+x^2)/G(x) - 1)/2
where F(x) is the e.g.f. of A179200.
EXAMPLE
E.g.f: G(x) = 2*x^2/2! - 6*x^3/3! + 12*x^4/4! + 200*x^5/5! +...
The e.g.f. of A179200, F(x), begins:
F(x) = x - 6*x^3/3! + 60*x^4/4! - 600*x^5/5! + 5880*x^6/6! - 38640*x^7/7! - 624960*x^8/8! +...
The i-th iteration of (x + x^2) = H(x) = F(x) + i*G(x), begins:
H(x) = x + i*x^2 - (1 + i)*x^3 + (5 + i)*x^4/2 - (15 - 5*i)*x^5/3 + (49 - 52*i)*x^6/6 - (23 - 83*i)*x^7/3 - (93 + 427*i)*x^8/6 + (15652 + 18537*i)*x^9/126 - (61567 + 24585*i)*x^10/126 + (369519 - 42094*i)*x^11/252 - (1743963 - 1222750*i)*x^12/504 + ...
where H(F(x) - i*G(x)) = x.
PROG
(PARI) {a(n)=local(M=matrix(n+1, n+1, r, c, if(r>=c, binomial(c, r-c))), L=sum(k=1, #M, -(M^0-M)^k/k), N=sum(k=0, #L, (I*L)^k/k!)); if(n<1, 0, imag(n!*N[n, 1]))}
CROSSREFS
KEYWORD
sign
AUTHOR
Paul D. Hanna, Jul 02 2010
STATUS
approved